An investigation of normal and submerged condition on microstructural and tribological properties of friction stir processed AZ91-D magnesium alloy. (2nd January 2017) - Bhadouria, N.; Thakur, L.; Kumar, P.; Arora, N.
ABSTRACT: A comparative study of micro-structural transformations and tribological properties of the friction stir processed AZ91-D magnesium (Mg) alloy in normal friction stir processing (NFSP) and submerged friction stir processing (SFSP) conditions was carried out. The optimum parameters used for processing were tool rotational speed of 1000 rpm/min, 50 mm/min of transverse speed and 6 numbers of passes. A significant reduction in grain size (28.7% and 13.1%) and increase in micro-hardness (14.55% and 8.92%) along depth and width of stir zone (SZ) of SFSPed specimen has been achieved as compared to NFSPed specimens. This change can be attributed to the dynamic recrystallisation and removal of excess frictional heat leading to inhibited post-grain growth in the processed alloy. Pin-on-disc sliding wear testing was conducted to compare the wear performance of NFSPed and SFSPed specimens. The SFSPed specimen has shown an improved wear resistance as compared to NFSPed specimens. The major prevailing wear mechanisms were abrasion, delamination, oxidation and mild plastic deformation.